Synthesis of some new substituted imines from aldehydes and ketones derived from quinolinic acid - Fathi, Anwar Abdulghani; Al Jawaheri, Yassir Shakeeb; Ismaee, Shaimaa Samir (Eclética Química, 2023)
In this paper, some substituted imines compounds have been prepared from quinolinic acid as a starting material. Firstly, the quinolinic acid was treated with acetic anhydride and acetic acid to form furo[3,4-b]pyridine-5,7-dione (1); the resulting compound was heated with urea to form 5H-pyrrolo[3,4-b]pyridine-5,7(6H)-dione (2). After that, it was treated with potassium hydroxide to give potassium 5,7-dioxo-5,7-dihydropyrrolo[3,4-b]pyridin-6-dione, which was directly and easily converted to 6-(2-([1,1'-biphenyl]-4-yl)-2-oxoethyl)-5H-pyrrolo[3,4-b]pyridine-5,7(6H)-dione (3) by the reaction with 1-([1,1'-biphenyl]-4-yl)-2-bromoethan-1-one. Finally, the resultant compound reacted with substituted aniline to give imines (4, 5). Secondly the quinolinic acid converted to 4-(5,7-dioxo-5,7-dihydro-6H-pyrrolo[3,4-b] pyridin-6-yl) benzenesulfonyl chloride according to our previous work, then treated with p-hydroxy acetophenone or p-hydroxy benzaldehyde to form 4-substituted bezyloxy 4-(5,7-dioxo-5,7-dihydro-6H-pyrrolo[3,4-b] pyridine-6-yl) benzenesulfonate (6, 7), which were finally treated with substituted aniline to form new substituted imines (8–12).